2020
DOI: 10.2217/fon-2019-0820
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Long Noncoding RNA B3GALT5-AS1 as a Diagnostic Biomarker of Colorectal Cancer

Abstract: Aim: Long noncoding RNA (lncRNA) B3GALT5-AS1 has been reported as a biomarker for cancer monitoring. This research aims to identify serum long noncoding RNA B3GALT5-AS1 as a new biomarker for the diagnosis of colorectal cancer (CRC) and evaluate its clinical value. Materials & methods: Serum B3GALT5-AS1 expression levels were measured by quantitative real-time PCR. Results: The level of B3GALT5-AS1 in CRC patients was significantly lower than that of healthy patients (p < 0.0001). Further exploration va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In addition, increasing serum B3GALT5-AS1 level was related to histological differentiation and TNM stage. Therefore, B3GALT5-AS1 might be a novel potential diagnostic biomarker for CRC (Ding et al, 2020). Our preliminary experiment confirmed that Linc01836 was significantly higher in the serum of CRC than in healthy folks.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, increasing serum B3GALT5-AS1 level was related to histological differentiation and TNM stage. Therefore, B3GALT5-AS1 might be a novel potential diagnostic biomarker for CRC (Ding et al, 2020). Our preliminary experiment confirmed that Linc01836 was significantly higher in the serum of CRC than in healthy folks.…”
Section: Discussionsupporting
confidence: 68%
“… 233 Recently, B3GALT5‐AS1 has been reported to be related to TNM stage and histological differentiation. 234 There are also other lncRNA that regulated CRLM through ceRNA mode, for example MALAT1, SNHG14, SNHG7, H19, and LINC00485. Taken together, these lncRNA could be a therapeutic target and promising biomarkers for prognosis prediction of CRLM.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Multiple lncRNAs were abnormally expressed, thereby acting as vital modulators in the regulation of progression of various cancers including in CRC [ 6 , 7 ]. High-expressed lncRNA HOTAIR is responsible for the pathogenesis of aggressive colon cancer [ 8 ] and gastrointestinal stromal tumor [ 9 ]; NR2F2-AS1 with a high expression is predictive of a lower overall survival of patients with CRC [ 10 ]; serum B3GALT5-AS1 is low-expressed in CRC patients, which therefore could be regarded as a diagnostic biomarker for identifying CRC patients [ 11 ]. Previous research based on bioinformatics found 5 lncRNAs (AL117190.1, MEG3, COL4A2-AS1, LINC00184, and MIR22 HG) as vital prognostic factors for breast cancer patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%